Time for an Update: The Currency of Clinical Guidelines in Australia—A Cross‐Sectional Analysis - Heath White; Ethan Fernandes; Kristina Peduru‐Arachchige; Tari Turner; Steven McGloughlin; Steve McDonald (Medical Journal of Australia, 2026)
ABSTRACT Objectives Long‐term and chronic health conditions are associated with a significant burden of disease and economic impact in Australia. Although improving health outcomes requires a multifactorial approach, up‐to‐date clinical guidelines can optimise healthcare delivery by providing clinicians with evidence‐based, actionable recommendations. We aimed to determine the currency and key methodological characteristics of national clinical guidelines published in Australia and focussed on areas of highest prevalence and burden of disease. Study Design and Setting We conducted a cross‐sectional analysis by searching PubMed, the Guidelines International Network International Guidelines Library and Australian college and society websites in July 2025 for national clinical guidelines in the five areas of highest prevalence and burden of disease, as defined by the Australian Bureau of Statistics and Australian Institute of Health and Welfare, respectively. Information and metrics relating to time since publication, time since last evidence search and methods and processes (e.g., reporting of clinical questions and Population, Intervention, Comparison, Outcome [PICO] criteria and approval of the guideline by the National Health and Medical Research Council [NHMRC]) were tabulated and analysed. Results Thirty‐one guidelines published between 2002 and 2025 were identified, with most relating to diabetes or mental health. The mean times since publication and last search date were 8.6 and 9.8 years, respectively. Most provided details regarding clinical questions (77%), PICO criteria (61%), search strategies (68%) and other methodological considerations, however, fewer than half used Grading of Recommendations Assessment, Development and Evaluation (GRADE) to assess certainty of evidence or provided details regarding conflicts of interest (48% each). Of the 18 guidelines approved by the NHMRC, five were developed within the previous 5 years and remain approved. Conclusion For most high‐priority clinical conditions in Australia, there are no up‐to‐date evidence‐based guidelines available to support clinical decision‐making. Guideline developers and funders should invest more energy and resources into planning for updates and ensuring that methods and processes are optimised to facilitate this, such as considering a living approach.